Stereotaxic surgery under X-ray guidance in the rhesus monkey, with special reference to the amygdala. - Aggleton, J; Passingham, R (1981)
The anterior/posterior (AP) positions of three subcortical regions; the amygdala, supra-optic nucleus of the hypothalamus and mammillary bodies, were estimated with respect to the skull in 35 rhesus monkeys (Macaca mulatta). The distances from the external auditory meatus, from which stereotaxic coordinates are typically derived, to these subcortical nuclei were found to be highly variable. In contrast the posterior tip of the sphenoid bone, which was visualized on lateral radiographs, provided a landmark at a remarkably constant AP distance from these nuclei. This landmark was used to guide a series of a amygdaloid lesions and injections. The accuracy of these operations strongly suggested that the posterior tip of the sphenoid bone could be used to predict not only the AP but also the height of the amygdala. It is proposed that this radiographic technique could be applied to other hypothalamic and basal forebrain regions.